PROJECT LEARNING - EFFECTIVE ALTERNATIVE EDUCATION STUDENTS USING ICT - BURIANOVA, Maria; MAGDIN, Martin (Trends in education, 2009)
Project learning is one way to link the classical training with modern, efficient and motivating way. In carrying out such type of education is informationcommunication technologies (ICT), using the multimedia elements, essential and indispensable part. Preparation of e-learning training module, the content will be designed specifically for teachers of the subject technology, represents the support of teachers who implemented the new, progressive education, which include the project lessons.
Keywords: technical training; project teaching; information and communication technologies; e-learning.